Evidence-Based Treatment of Severe Psoriasis by Individualised Homoeopathy: Case Reports - Gupta, Sapna; Nair, Ashwini; Rana, Manoj Kumar (Homœopathic Links, 2022)
Psoriasis is a chronic skin disease with manifestations in skin, nails and joints. The disease usually runs a long course of remission and relapses, and is usually worse in winters. Psoriasis Area and Severity Index (PASI) score above 15 is considered to be an independent criterion for classifying a case as severe psoriasis. The conventional systemic therapy controls the symptoms but is costly and has known adverse effects. Individualised homoeopathic treatment has a potential role in providing safe and cost-effective treatment in psoriasis. In this article, three cases of severe psoriasis vulgaris treated with Homoeopathy at Bakson Homoeopathic Medical College and hospital are presented. Two cases were under treatment for a period of 20 months and one case received treatment for 24 months. Significant reduction (60–100%) in PASI score was observed with individualised homoeopathic treatment.
Keywords: psoriasis; homoeopathy; Individualised homoeopathic treatment; repertory; PASI score